EVALUASI MUTU PANEN KELAPA SAWIT DI PT. SENTOSA KALIMANTAN JAYA - Bella Viesta Haloho; Puspita; Yuanita (Politeknik Pertanian Negeri Samarinda, 2021)
The objective of the research is to evaluate the quality of harvesting oil palm fresh fruit bunches (FFB) correlated to the harvest system implemented by two afdelings in the oil palm plantation company, PT. Sentosa Kalimantan Jaya. The research employs descriptive design, with qualitative approach, purposive sampling and snowball sampling using questionnaires, and documentation. The research reveals that the characteristics of harvesters from two afdelings are dominated from the productive age and educated at elementary school. The harvesters in afdeling 2 have more experience than afdeling 4. Afdeling 2 provides better quality of FFB than afdeling 4, it comprises ripe fruit was 86.91%, abnormal was 1.07% and long stalk was 0%. Meanwhile, afdeling 4 comprises raw fruit was 1.32%, ripe fruit was 79.97%, and over ripe fruit was 12.88%. Both afdelings have permanent design of harvest system comprise the percentage of loose fruit, sengkleh stems, under pruning and over pruning which are beneath the standard. The under pruning interferes the process of cutting fruit, meanwhile the over pruning would potentially be able to reduce average bunches weight and produce male flowers dominantly. As a result, it can be deduced that the main factor affects the quality of permanent design of harvest system, and the quality of oil palm fresh fruit bunches is the harvesters’ experience of work. Afdeling 2 has 6 harvesters working for >5 years or 46.2%. The overall findings reveal that the longer harvester's working period, the labor productivity of harvesting oil palm will increase.